Environmental Effects of Capital Income Taxation - A New Double Dividend? - Hendrik Ritter; Marco Runkel; Karl Zimmermann (ZBW – Leibniz Information Centre for Economics, 2019)
We analyze a n-country, two-period Nash tax competition game to evaluate Sinn's proposal to use capital income taxation as a means to decelerate fossil fuel ex- traction (Sinn, 2008). The interest and discount rate is determined on a perfectly competitive consumer loan market on which the resource extractor acts as the loan supplier. Our first result is that, with perfectly identical countries, tax rates are inefficiently low in the Nash equilibrium of the tax competition game since the tax distortion and the environmental externality are not taken into account. The sec- ond result is that, in an asymmetric setting with resource-exporting and -importing countries, the tax can turn into a subsidy in the exporting country. Moreover, we show that partial cooperation of the importers is always beneficial to them, but can be harmful to the exporter. Finally, we identify cases where full cooperation is self-enforcing.
Keywords: H21; H23; Q38; Q54; 330; Capital taxation; Green paradox; Non-renewable resources